2010
DOI: 10.1177/0193723510377327
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Space: Inclusion, Exclusion, and Accommodation at the British Golf Club Before 1914

Abstract: The pre-1914 British golf club exhibited bonding social capital formation rather than bridging, seeking to exclude rather than include. Generally the course, but especially the clubhouse, were sites for males of similar social background to meet in a homosocial environment, one protected by cost and membership policies. Segmentation of clubs within the same geographical area allowed for further social differentiation between men from different occupational groups. Numerous golfing societies also brought men to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…Just as an example, the dress code defined in the rules of the game and societal expectations was very rigid and for a long time, limitative of female performances: ''in the 1890s the majority of women golfers complied with what was expected and appeared in clothing which hampered to some degree their style of play'' (George, 2009, p. 335). Vamplew (2010) advances a contextualisation of the beginning of golf within this strict society referring to the exclusion of women from clubhouses. Further, George et al (2007) and George (2009) highlight gender discrimination in golf, providing a consistent historical perspective of constraints women had to face in order to play.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as an example, the dress code defined in the rules of the game and societal expectations was very rigid and for a long time, limitative of female performances: ''in the 1890s the majority of women golfers complied with what was expected and appeared in clothing which hampered to some degree their style of play'' (George, 2009, p. 335). Vamplew (2010) advances a contextualisation of the beginning of golf within this strict society referring to the exclusion of women from clubhouses. Further, George et al (2007) and George (2009) highlight gender discrimination in golf, providing a consistent historical perspective of constraints women had to face in order to play.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite all this, numerous women have persisted in the game and can be considered from two perspectives (George, 2010;Vamplew, 2010):…”
Section: Literature Reviewmentioning
confidence: 99%
“…He also suggested the industrial revolution in 1890 (Ceron-Anaya, 2010) brought with it the fact that to increase productivity people could divide their time between work and leisure (Veblen, 2011). It is suggested that different levels of income will lead to different types of sports and there is no doubt that golf is related to financial status (Neo, 2010;Parker, 2012;Reis & Correia, 2013;Vamplew, 2010). Therefore, the following hypothesis is proposed: H3: The cultural factor has a positive influence on the golf industry in China in relation to the feature of luxury product.…”
Section: Key Market Growth Factors That Influence "Luxurisation" Of Gmentioning
confidence: 99%
“…Golf is historically consecrated as a sport practice exclusive of high social and economic classes, and so, has found many obstacles to claim itself as a popular sport (Vamplew, 2010). This dimension is also a determining factor to realize the level of integration/rejection that golf assumes in social context.…”
Section: Golf Demand and Golf Destinations: Issues And Dimensionsmentioning
confidence: 99%